PENDEKATAN PLANNING AS SOCIAL LEARNING DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI KOPERASI DESA MERAH PUTIH DI DESA MARINDAL II, KABUPATEN DELI SERDANG - Damanik, Rolinta; Erika Revida; Ebenezer Siburian; Yandri Petra Perangin-angin (Yayasan Nusantara Hasana Berdikari, 2026)
This study analyzes the implementation of the Planning as Social Learning approach in community economic empowerment through Koperasi Desa Merah Putih Marindal II in Patumbak, Deli Serdang Regency. A qualitative case study approach was employed. Data were collected through semi-structured interviews with the cooperative chairperson, the Head of the Cooperative and Micro, Small, and Medium Enterprises Office of Deli Serdang Regency, and two active cooperative members. The findings indicate that the cooperative was established mainly as a follow-up to Presidential Instruction No. 9 of 2025, with limited member participation in planning and decision-making. Most strategic decisions remain dominated by the management board. Informal learning among members has begun through shared business experiences and online communication, but structured collective evaluation is still lacking. Economically, the cooperative has provided benefits to micro-entrepreneurs by improving access to supplies and strengthening local networks. However, limited capital, managerial capacity, and low public trust remain significant challenges. The study concludes that the cooperative is still in the early stage of institutional development and requires stronger member participation and more structured evaluation mechanisms.